ESTUDO COMPARATIVO DA ATIVIDADE ELETROCATALÍTICA DA REDUÇÃO DE OXIGÊNIO POR NANOPARTÍCULAS DE ÓXIDOS METÁLICOS (Fe2O3 e Co3O4) EM MEIO ÁCIDO. - ALVES, Ismael Carlos Braga (2018)
This work presents a comparative study about the oxygen reduction reaction (ORR), catalyzed by nanoparticles of metal oxides (Fe2O3 and Co3O4) anchored on the vitreous carbon electrode (VCE) surface. The nanoparticles were synthesized using the modified polymer precursor method (Pechini). The nanomaterials were characterized by Fourier Transform Infrared (FTIR)Spectroscopy, and X-ray diffraction (XRD) techniques. The estimated average size were 20.47 and 31 nm, respectively, for iron and cobalt oxides. Electrochemical Impedance Spectroscopy (EIS) showed that VCE/Fe2O3 has a lower charge transfer resistance (Rtc) when compared to ECV/Co3O4. The electrochemical activity of the RRO was studied by cyclic voltammetry (CV) and rotating disk voltammetry experiment in acid solution. The number of electrons for the electrocatalytic reduction of oxygen was found to be 3.58 and 2.57 for ECV / Fe2O3 and ECV / Co3O4, respectively. The response of the electroctalysts for the RRO was also verified in the presence of methanol, and both catalysts presented no significant lost of the electrocatalytic activity for RRO. However the ECV/Fe2O3 presented higher catalytic activity (higher current) in this study. These results indicated that ECV/Fe2O3 is more efficient for the RRO, from the electrocatalytic point of view.